Nanomedicines with high drug availability and drug sensitivity overcome hypoxia-associated drug resistance. (March 2023) - Liu, Yi; Dong, Wang; Ma, Yinchu; Dou, Jiaxiang; Jiang, Wei; Wang, Li; Wang, Qin; Li, Shuya; Wang, Yucai; Li, Min
Abstract: Tumor hypoxia heterogeneity, a hallmark of the tumor microenvironment, confers resistance to conventional chemotherapy due to insufficient drug availability and drug sensitivity in hypoxic regions. To overcome these challenges, we develope a nanomedicine, NPHPaPN, constructed with hyaluronic acid (HA) grafted with cisplatin prodrug and PEG-azobenzene for hypoxia-responsive PEG shell deshielding and loaded with a DNA damage repair inhibitor (NERi). After arriving at the tumor site, NPHPaPN deshields the PEG shell in response to hypoxia due to the enzymolysis of azobenzene and thus exposes HA. The exposed HA binds to the highly expressed CD44 on cisplatin-resistant tumor cells and mediates drug internalization, thus increasing drug availability to hypoxic tumor cells. After intracellular hyaluronidase-mediated cleavage, the HA NPs release the cisplatin prodrug and NERi, and cause enhanced DNA damage and consequent cell death, thus enhancing the drug sensitivity of hypoxic tumor cells. Eventually, NPHPaPN achieves distinct tumor growth suppression with an ∼84.4% inhibition rate. Highlights: NPHPaPN improves the availability and sensitivity of cisplatin in hypoxic tumors. NPHPaPN is composed of HA grafted with cisplatin, PEG-azobenzene, and a NERi. NPHPaPN deshields PEG and exposes HA in hypoxic tumors, increasing drug availability. NPHPaPN inhibits DNA damage repair, increasing drug sensitivity in hypoxic tumors. Through synergyzing these aspects, NPHPaPN significantly suppresses tumor growth.